ผลของการจัดกิจกรรมการเรียนรู้คณิตศาสตร์โดยใช้โมเดลการแก้ปัญหาที่เน้นกระบวนการรู้คิด ร่วมกับ Four Corners and a Diamond Graphic Organizers ที่มีต่อความสามารถ ในการให้เหตุผลและการสื่อสารทางคณิตศาสตร์ของนักเรียนมัธยมศึกษาปีที่ 2 - วังเวชช์ เพาพงา; ทำสวน จงกล (An Online Journal of Education, 2018)
The purposes of this research were to 1) compare mathematical reasoning and communication abilities of the students learning by using an organizing learning activities using the problem solving model of metacognitive process and Four Corners and a Diamond Graphic Organizers between, before and after learning, 2) compare mathematical reasoning and communication abilities of students between experimental group and control group, and 3) study the mathematical reasoning and communication abilities of students learning by using an organizing learning activities using the problem solving model of metacognitive process and Four Corners and a Diamond Graphic Organizers. The subjects were eighth grade students of Ammartpanichnukul School in Krabi, in the second semester of academic year 2016, which was purposive sampling. There were 49 students in the experimental group and 50 students in the control group. The experimental instruments constructed by the researcher were lesson plans focusing on the organizing learning activities using the problem solving model of metacognitive process and Four Corners and a Diamond Graphic Organizers and conventional plans. The instruments for data collection were mathematical reasoning ability tests and mathematical communication ability tests. The data were analyzed by using arithmetic mean, standard deviation, and t-test and content analysis. The results of the study revealed that 1) the mathematical reasoning and communication abilities of students in the experimental group were higher than those before the experiment at a .05 level of significance, 2) the mathematical reasoning and communication abilities of students in the experimental group were higher than those of the students in the control group at a .05 level of significance, and 3) the mathematical reasoning and communication abilities of students in the experimental group were developed in positive direction.